Obstructed Groin Hernia in a Tropical African Population - Ajao, Oluwole G. (1979)
In a 15-month period, at the University College Hospital, Ibadan, 44 cases of obstructed hernia were treated by emergency operation. More than 94 percent were inguinal, but femoral hernia was not common. The ratio of females to males was 1:6.4, and more than 68 percent of hernias occurred on the right side. The youngest patient was two weeks old. One incarcerated hernial sac contained an ileoileal intussusception and a segment of sigmoid colon.